A rare case of polypoid primary anorectal melanoma with subsequent giant stomach metastasis: a gastrointestinal involvement of both primary and metastatic mucosal melanoma - Vincenzo De Giorgi; Federica Scarfi; Carlo Boselli; Giacomo Sacchetti; Nicola Natalizi; Danilo Castellano; Piero Covarelli (PAGEPress Publications, 2021)
Introduction: Melanoma can involve the gastrointestinal apparatus as both primary and metastatic lesions. Primary anorectal mucosal melanoma (ARMM) and metastatic gastric melanoma are rare entities and usually resulted in a poor prognosis. Case: We presented a case of a 61-year-old man who after the complete excision of an ARMM developed a gastric metastasis after almost three years form the complete tumour excision. Upon esophagogastroduodenoscopy, a giant ulcered mass resulted in melanoma metastasis. The patient underwent a near-total gastrectomy. After five months of follow-up, the patient is disease-free. Conclusion: The incidence of ARMMs is increasing, highlighting the necessity of new prevention and treatment strategies in order to achieve a better prognosis for these patients. There are no known risk factor for ARMMs but surgery, together with the combination of anti-CTLA-4 and anti-PD-1 antibodies, are promising therapeutic options. Early and aggressive treatments are required, together with a strict multidisciplinary approach.